2001
DOI: 10.1063/1.1413718
|View full text |Cite
|
Sign up to set email alerts
|

Carbon acceptor doping efficiency in GaAs grown by metalorganic chemical vapor deposition

Abstract: Carbon doping efficiency in GaAs grown by metalorganic chemical vapor deposition using intrinsic and extrinsic doping sources is studied. Independent of the carbon source, carbon hydrogen complexes are systematically present and depending on the growth conditions, carbon dimers can be present and form complexes with hydrogen as well. Carbon–hydrogen related complexes and dimers reduce the hole concentration decreasing the doping efficiency. Additionally, the carbon dimer introduces a deep level, decreases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Intrinsic carbon incorporation in MOVPE-grown GaAs layers is enhanced at low growth temperatures and V/III stoichiometric ratio between the metalorganic precursors in the vapour phase, due to the incorporation of methyl radicals on substitutional As sites [6]. Doping levels as high as 10 19 cm -3 were obtained for GaAs by using trimethyl gallium (TMGa) and arsine (AsH 3 ) or trimethyl arsenic (TMAs) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic carbon incorporation in MOVPE-grown GaAs layers is enhanced at low growth temperatures and V/III stoichiometric ratio between the metalorganic precursors in the vapour phase, due to the incorporation of methyl radicals on substitutional As sites [6]. Doping levels as high as 10 19 cm -3 were obtained for GaAs by using trimethyl gallium (TMGa) and arsine (AsH 3 ) or trimethyl arsenic (TMAs) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…If carbon would be incorporated on interstitial sites, an effect on the lattice contraction would be expected. It is reported that carbon-hydrogen and carbon dimer complexes in as-grown GaAs reduce the electrical activation degree of carbon acceptors [7]. We believe this to be true for AlGaAs as well.…”
Section: Influence Of Growth Parametersmentioning
confidence: 83%
“…As seen in Fig. 3, the V/III ratio of 0.7 contains C-H and C 2 -H complexes; however, only the C-H complex accounts for the gain-drift because the C 2 -H complex does not ionize at RT due to its deep acceptor level [18]. We thus conclude that the V/III ratio of 25 contains less of C-H complex and no C 2 -H complex, which leads to a high thermal stability.…”
Section: Hydrogen-related Defects In P-gaasmentioning
confidence: 94%